Proteinuria Severity in Lupus Nephritis is Associated with Anti-dsDNA Level and Immune Complex Deposit Location in Kidney - Engli, Katherina; Handono, Kusworini; Eko, Mudjiwijono Handaru; Susianti, Hani; Gunawan, Atma; Kalim, Handono (Journal of Tropical Life Science, 2018)
Lupus nephritis (LN) is one of the manifestations of Systemic Lupus Erythematosus (SLE), with proteinuria being one of the clinical manifestations. The proteinuria pathogenesis is associated with anti-dsDNA antibody and the location of immune complex deposits within the kidney. This study aims to investigate the correlation of the severity of proteinuria with the location of immune complex deposits and the level of anti-dsDNA antibody in LN. Data were collected in cross-section. Fifty-three patients with LN in Saiful Anwar Hospital Malang, who underwent renal biopsy, were included. Hematoxylin-eosin staining and immunofluorescence analysis were used to assign subjects to different histopathological classes and determine the immune complex deposits. The spot urine samples were evaluated using the dipstick method for semi-quantitative proteinuria. The anti-dsDNA antibody levels were evaluated using the enzyme-linked immunosorbent assay (ELISA). Turbidity and enzymatic tests were conducted to elucidate urine protein and creatinine content, respectively. The level of proteinuria is significantly different among the different locations of immune complex based on the dipstick and protein/creatinine methods (p = 0.021 and p = 0.005, respectively). There was a significant correlation between anti-dsDNA antibody level and the severity of proteinuria (r = 0.326 based on dipstick and r = 0.28 based on protein/creatinine method). Thus, proteinuria in LN is determined by anti-dsDNA level and the location of immune complex deposits in the kidney.